Effectiveness of Peer Education on Self Efficacy, Commitment and Quality of Life on Breast Cancer Patients - Diana Pefbrianti; Diana Hardiyanti (Proceeding of International Conference on Science, Health, And Technology, 2019)
Breast cancer was the most common cancer in women, mortality rate and morbidity continued to increase, cases of breast cancer found to be more severe and cause death. Peer education education could be used to improve the quality of life of breast cancer patients so that patients have the spirit to improve the health. The purpose of this study was to examine the effectiveness of peer education on self efficacy, commitment and quality of life in patients with breast cancer. The design of this study was quasy experiment researched with pre and post control group design with a total of 36 respondents. The research was conducted at POSA RSUD Dr. Soetomo Surabaya was divided into 18 respondents for peer education group and 18 for control group. The sampling method used was simple random sampling. Independent variable in this study were peer education while the dependent variable in this study were self efficacy, commitment, and quality of life. Data were collected by questionnaire and analyzed by manova Results: The result of statistical test showed that there was influence of peer education on self efficacy (p = 0,006), there was no influence between peer education to commitment (p = 0,072), there was influence of peer education on quality of life (p = 0,001). In general, peer education education affect the self efficacy, commitment and quality of life when done posttest with manova (p = 0,023) . Breast cancer survivors experienced an increased in self efficacy and quality of life in both intervention groups. This was related to verbal persuasion where the individual got the influence or suggestion and belief that she was able to overcome the problem to be faced. Researchers were further advised to conduct similar research by adding family empowerment to better engage the family.